Profil Deskriptif Respon dan Sikap Belajar Siswa pada Materi Pengukuran di SMA Negeri 3 Muaro Jambi - Pratama, Andrea Yuda (Universitas Sains dan Teknologi Komputer, 2025)
This research was motivated by the need to evaluate the effectiveness of the Measurement learning method in high school, which is often difficult to understand through conventional lecture methods due to the lack of visualization. This study aims to compare the profile of student attitudes and learning responses between groups taught with the Lecture Method (Class X-E1) and the Video Demonstration Method (Class X-E2) at SMA Negeri 3 Muaro Jambi. Using a comparative descriptive quantitative approach, data were collected through an attitude questionnaire containing 30 statements measuring interest, engagement, and motivation. Data analysis was conducted descriptively without inferential statistical tests. The results showed a striking difference between the two groups. The video demonstration group (X-E2) achieved a higher average score and was categorized as Very Good, while the lecture group (X-E1) was in the Good category with lower scores, especially in engagement and interest. These findings indicate that video demonstrations are more effective in attracting attention, increasing motivation, and creating an engaging learning experience. This study recommends the need for a shift in teaching methods from traditional lectures to the integration of technological media. Video demonstrations are not just tools, but essential strategies for building positive learning attitudes that are the foundation for improving cognitive learning outcomes.